Grit dan Mindfulness pada Mahasiswa yang Bekerja di Kota Bandung - Oktapiana, Diana; Annisa, Nida Muthi; Firdasannah, Astri (Universitas Brawijaya, 2024)
There are various reasons various reasons why students choose to study while working, despite the risks involved. Students who work take on dual roles as both workers and students, requiring them to remain enthusiastic and focused in order to successfully complete their studies. This study aims to examine the relationship between grit and mindfulness in students who work in the city of Bandung. It employs a quantitative method with a correlational design. The research subjects were 184 active undergraduate regular class students who were studying while working in the city of Bandung with an age range of 18-25 years. Data were collected using the grit scale and the Mindfulness Attention Awareness Scale (MAAS). The data analysis technique used is Product Moment correlation technique. The results revealed a positive, albeit weak, relationship between grit and mindfulness among working students in Bandung. In other words, higher levels of grit are associated with greater mindfulness, while lower levels of grit correspond to reduced mindfulness.